2022
DOI: 10.1155/2022/5222760
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Big Data Technology to Promote Agricultural Structure Adjustment and High-Quality Development of Modern Agriculture

Abstract: The implementation of the strategy of rural revitalization is a major ministerial work made by the Nineteenth National Congress of the Communist Party of China and is the general grasp of contemporary agriculture, peasants, and rural work. In recent years, with the rapid development of remote sensing technology and deep learning technology, the demand for the technology for the classification of crops on satellite remote sensing images based on deep learning technology has increased in agricultural insurance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…Savchenko IV (2019) discussed the development priorities of crop production in Russia and noted that high-yield and environmentally friendly crop cultivation relying on digital intelligent production technology is one of the country’s main development priorities [ 32 ]. Ju XX (2022) noted that big data technology can promote adjustments to the agricultural structure and the high-quality development of modern agriculture, and the development of modern agriculture cannot be separated from agricultural industrialization, agricultural globalization, agricultural digitalization, agricultural integration, agricultural structure adjustment and agricultural innovation [ 33 ]. Shen ZY (2022) studied the relationship between China’s agricultural digital transformation and green growth and found that China’s provincial agriculture has experienced significant green growth driven by technological progress, and the popularization of the internet and digital technology has indeed promoted sustainable agricultural development [ 34 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Savchenko IV (2019) discussed the development priorities of crop production in Russia and noted that high-yield and environmentally friendly crop cultivation relying on digital intelligent production technology is one of the country’s main development priorities [ 32 ]. Ju XX (2022) noted that big data technology can promote adjustments to the agricultural structure and the high-quality development of modern agriculture, and the development of modern agriculture cannot be separated from agricultural industrialization, agricultural globalization, agricultural digitalization, agricultural integration, agricultural structure adjustment and agricultural innovation [ 33 ]. Shen ZY (2022) studied the relationship between China’s agricultural digital transformation and green growth and found that China’s provincial agriculture has experienced significant green growth driven by technological progress, and the popularization of the internet and digital technology has indeed promoted sustainable agricultural development [ 34 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…SA has become a global trend in the development of agricultural modernization 4 , with developed countries using high-level agricultural technology and agricultural subsidy support as a carrier 3 and capital flows and market expansion as a backing, objectively forming a squeeze and control on the development of agricultural industries in developing countries. Therefore, for more than a decade in a row, China has had relevant documents dealing with SA, which is an important initiative to break through the current bottleneck of traditional agricultural development 5 , achieve high-quality, high-efficiency and sustainable development of agriculture 6 , 7 , and take the lead in modernising agriculture and rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if China wants to safeguard the steady development of agriculture under the constraints of resources and environment, it must change the way of agricultural development, take the path of high-quality agricultural development, and hold the initiative of agricultural development rmly in its own hands, so as to achieve the transformation from a large agricultural country to a strong agricultural country. For more than a decade in a row, China has published documents related to SA, which is an important initiative to break through the current bottleneck of traditional agricultural development 5 , achieve high-quality, high-e ciency and sustainable development in agriculture 6,7 and take the lead in modernising agriculture and rural areas.…”
Section: Introductionmentioning
confidence: 99%